Quantifying the green hydrogen demand across key sectors in Aotearoa New Zealand: Implications for electricity generation - Emvula, Thekla; Brent, Alan (Archives of Sustainable Energy Systems, 2025)
The transition to green hydrogen presents a great opportunity for Aotearoa New Zealand to meet its long-term climate targets while decarbonising energy intensive sectors. With over 80% of electricity already generated from renewable sources, the country is well-positioned to produce green hydrogen through water electrolysis. However, the extent to which hydrogen demand may impact electricity generation capacity remains underexplored. This study quantifies projected hydrogen demand across four key sectors: steel, heavy-duty transport (trucks and coaches), methanol production, and fertilizer manufacturing, from 2025 to 2050. Historical production and activity data were collected from national and international sources and used to project future sectoral activity. Hydrogen demand was estimated under both ideal stoichiometric and real-world adjusted efficiency scenarios. These values were then converted into electricity requirements using efficiency benchmarks for Proton Exchange Membrane (PEM) and Solid Oxide Electrolyser Cell (SOEC) technologies. The results show that the transport and methanol sectors exhibit the highest hydrogen demand, followed by fertilizers and steel. Under real-world assumptions, electricity demand to produce hydrogen could reach between 30 and 55 terawatt-hours annually by 2050, potentially exceeding Aotearoa New Zealand’s current generation capacity. The findings highlight the importance of aligning hydrogen development with renewable electricity expansion and infrastructure planning. The study provides a replicable modelling approach for emerging hydrogen economies, particularly in the Global South. It contributes to the evolving body of knowledge by offering a sector-specific assessment of hydrogen demand, integrating technological parameters with national energy system planning, and informing future hydrogen strategy development in Aotearoa New Zealand and beyond.